2012
DOI: 10.1111/j.1440-1819.2011.02318.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of angiotensin I‐converting enzyme (ACE), but not angiotensin II type I receptor (ATr1), has a gender‐specific role in panic disorder

Abstract: Aims: Angiotensins were shown to have some role in the development of panic disorder (PD). In this study, we aimed to determine the frequency of polymorphisms in two angiotensin-related genes, angiotensin I-converting enzyme (ACE) and angiotensin II type I receptor (ATr1), in a sample of Turkish patients with PD and to evaluate their association with PD development. Methods: Polymerase chain reaction and restriction fragment length polymorphism was used to analyzeATr1 A1166C polymorphism, and only polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…The prevalence of the ACE gene polymorphism D allele is 39% in Japanese, 54% in European Caucasian, 56% in American Caucasian, and 60% in African American (27,28) populations. Our population consisted of Turkish Caucasians, and the genotype and allele frequencies found in this study were similar to the previously reported frequencies in Turkish populations (29,30). The D allele frequency has been reported to be 60.1% (29) or 64.0% (30) in healthy Turkish populations.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The prevalence of the ACE gene polymorphism D allele is 39% in Japanese, 54% in European Caucasian, 56% in American Caucasian, and 60% in African American (27,28) populations. Our population consisted of Turkish Caucasians, and the genotype and allele frequencies found in this study were similar to the previously reported frequencies in Turkish populations (29,30). The D allele frequency has been reported to be 60.1% (29) or 64.0% (30) in healthy Turkish populations.…”
Section: Discussionsupporting
confidence: 73%
“…Our population consisted of Turkish Caucasians, and the genotype and allele frequencies found in this study were similar to the previously reported frequencies in Turkish populations (29,30). The D allele frequency has been reported to be 60.1% (29) or 64.0% (30) in healthy Turkish populations. We found a D allele frequency of 62.7% in the present study, which appears to be similar to the reported frequencies.…”
Section: Discussionsupporting
confidence: 73%
“…It seems that, among the factors that provide hypertension in offspring from mothers subjected to high-sodium intake during pregnancy, RAS is the main controlling system. Recently, Bayoglu et al demonstrated that angiotensinogen, angiotensin converting enzyme [27], AT1R, and AT2R expression altered following maternal high-salt intake. They suggested that high-salt diet during pregnancy affects expression of the renal key elements of RAS in fetus and offspring [28].…”
Section: Discussionmentioning
confidence: 99%
“…While it was reported that bipolar disorder was not associated with I/D polymorphism 27 , another study suggested that it was associated with I/D genotype in the Asian race 28 . ACE gene polymorphism was reported not to be related to panic disorder 29,30 , although the frequency of I allele is higher in men than women 31 . Another study stated that there was an association between ACE gene polymorphism and MDD only in female patients 32 , as consistent to our results.…”
Section: Discussionmentioning
confidence: 99%